A dictionary of communication and media studies - Watson, James, 1936-; Hill, Anne, 1952- (London ; New York : E. Arnold ; New York, NY : Distributed by Routledge, Chapman, and Hall, 1993)
This dictionary has become a unique resource for students and teachers in the field of communication and media studies. It brings together a large amount of essential information regarding current media policy and practice, and also provides clear and lively explanations of the many concepts and models which make up communication theory. In its third edition, the dictionary has been brought completely up-to-date, with over 100 new definitions reflecting the latest theories, research findings and developments in media practice. The new entries include information on recent, far-reaching developments in broadcasting and consider the increasing influence of transnational corporations over cultural discourse and activity. There is also expanded coverage of important issues such as feminism, racism and sexism.
Spine title: A dictionary of communication & media studies.
All age.
Keywords: Communication -- Dictionaries; Mass media -- Dictionaries; Mass media -- Dictionnaires anglais